The Implementation of Basic Principles of Journalism in Citizen Journalist’s News on NETCJ - Erwin Kartinawati; Rahmat Wisudawanto (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
The face of mass media has transformed extraordinarily after internet presence. The content was no longer the dominance of media because technology and the public can participate in producing and publishing news, which raised the phenomenon of citizen journalism. Mainstream media captured this phenomenon by bringing up programs based on news that sent by citizens. This research aimed to see the implementation of basic principles of journalism on news that sent by citizens, and the causes that influenced it, on www.netcj.co.id. The basic tenets seen were accuracy and fairness. The quantitative content analysis was used to see the first problem; then, the second problem was explored by interviews. The result showed that news sent by citizens on NETCJ mostly was inaccurate (55.17%) and unfair (42.92%). The differences in educational background and experience, the status of citizen journalists, and newsroom policy were the cause of the problem.